تقييم جودة النتائج الامتحانية في المقررات باستخدام تحليل التوزيع التكراري لها مثال كلية الاقتصاد بجامعة تشرين (Latakia University Journal - Economic and Legal Sciences Series, 2017)
إنّ جودة عملية التدريس في الجامعة يصعب قياسها وتحديد مقدار جودتها، لأنها تتأثر بالعديد من العوامل المادية والبشرية والإدارية، مما دعانا إلى استنباط أسلوب كمي لتقييم وقياس جودة النتائج الامتحانية في المقررات الدراسية الجامعية من خلال تحليل التوزيع التكراري لنتائج كل مقرر على حدة ولكل السنوات, سواءً كانت الكلية نظرية أو تطبيقية، ومن ثم إجراء اختبار مطابقة للتوزيع التكراري الفعلي مع التوزيع التكراري النظري لتوزيع بيتا المعياري باستخدام اختبار كاي مربع، ومن النتائج التي تمّ الحصول عليها:1 ـ استنباط علاقة رياضية لقياس جودة النتائج الامتحانية في المقررات الجامعية.2 ـ حساب جودة النتائج الامتحانية لبعض المقررات في بعض السنوات الأربعة في كلية الاقتصاد بجامعة تشرين.3 ـ إن جودة النتائج الامتحانية تختلف عن نسبة النجاح.The quality of the teaching process at the university are difficult to measure and determine the amount of quality, because they are influenced by many of the physical, human and administrative factors, which invited us to devise a quantitative method for evaluating and measuring the quality of the results the examination in the courses the university through distribution analysis Recurring of the results of each course separately and each year, either College was a theory or application, and then make a matching test for distribution with the actual distribution Recurring Recurring theoretical standard beta distribution using Chi-square test, and the results that have been obtained:1. devise mathematical relationship to measure the quality of the examination results in university courses.2. the expense of the quality of the examination results of some courses in some four years in the Faculty of Economics at the University of Tishreen.3. The quality of the examination results differ from the success rate.